Nivel de conocimiento sobre VIH-SIDA en los estudiantes de bachillerato sección diurna del Colegio Nueve de Octubre de la ciudad de Machala durante el período 2011-2012 - Salcedo Loayza, Melania Y. (2012)
We performed a prospective sudy in the Nueve de Octubre High School city of Machala in which 318 students were surveyed section 318 day period from 2011 to 2012 in order to determine the level of knowledge about HIV-AIDS.